Lc-Ms/Ms Profiling and Characterization of Active Components from Medicinal Gingers (Curcuma Xanthorrhiza and Zingiber Zerumbet) - Ruslay, Sharin (2006)
Ground fresh rhizomes of Zingiber zerumbet and Curcuma xanthorrhiza were exhaustively extracted using acetone, ethanol and water. Acetone extract of Z. zerumbet and ethanol extract of C. xanthorrhiza gave highest yield of crude extract. The crude extracts were fractionated between water and hexane, ethyl acetate and butanol. All the crude extracts and fractions were screened for antioxidant activity. Ethyl acetate and butanol fractions exhibited good antioxidant activity, of which ethyl acetate fractions from both plants showed strongest antioxidant activity.